2021
DOI: 10.3390/jcm11010147
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Radial Extracorporeal Shock Wave Therapy and Visual Feedback Balance Training on Lower Limb Post-Stroke Spasticity, Trunk Performance, and Balance: A Randomized Controlled Trial

Abstract: Stroke remains one of the leading causes of disability in adults, and lower limb spasticity, affected stance, and balance impact everyday life and activities of such patients. Robotic therapy and assessment are becoming important tools to clinical evaluation for post-stroke rehabilitation. The aim of this study was to determine in a more objective manner the effects of visual feedback balance training through a balance trainer system and radial extracorporeal shock wave therapy (rESWT), along with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(72 reference statements)
0
1
0
Order By: Relevance
“… 26 , 28 The results of our study are in line with other trials given that clinical and instrumental data supported the effectiveness of ESWT in reducing the grade of muscle spasticity in children with CP, as well as in post-stroke adults. 6 , 12 , 29 Positive effects of rESWT delivered during a CPT protocol were also noticed for outcomes such as sensorimotor and lower limb function, balance, and gait. A possible explanation for these positive changes after ESWT could be that in children with CP the plantar surface area increased, and consequently, the gait pattern also improved leading to better stability and balance control.…”
Section: Discussionmentioning
confidence: 95%
“… 26 , 28 The results of our study are in line with other trials given that clinical and instrumental data supported the effectiveness of ESWT in reducing the grade of muscle spasticity in children with CP, as well as in post-stroke adults. 6 , 12 , 29 Positive effects of rESWT delivered during a CPT protocol were also noticed for outcomes such as sensorimotor and lower limb function, balance, and gait. A possible explanation for these positive changes after ESWT could be that in children with CP the plantar surface area increased, and consequently, the gait pattern also improved leading to better stability and balance control.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanical stimulation induced by ESWT can increase blood flow [ 28 ], promote cellular responses, and enhance the functionality of affected muscles and joints, thereby improving overall balance and stability [ 34 ]. Several clinical trials and systematic reviews have investigated the effects of ESWT on balance ( Table 1 ) [ 35 ]. These studies have generally reported positive outcomes, with improvements in balance and postural control following ESWT treatment.…”
Section: Effects Of Eswt On Balance Improvement In Strokementioning
confidence: 99%